Method for improving wear resistance of high-plasticity refractory high-entropy alloy, high-entropy alloy and application thereof
By heating and quickly cooling high-entropy alloy samples under the protection of inert gas, a dense wear-resistant oxide layer is formed, which solves the problem of insufficient wear resistance of high-plastic refractory high-entropy alloys, and achieves a longer service life and excellent strong plasticity matching in biomedical implant applications.
Patent Information
- Application Number
- CN202410743463.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-06-11
AI Technical Summary
High plastic refractory high entropy alloys have insufficient wear resistance in biomedical implant applications, which leads to the easy production of fine particles such as wear chips and causing inflammation when they are in the body for a long time.
The high entropy alloy sample is heated to a preset temperature and kept warm under the protection of inert gas, and then the sample is quickly placed in a water-cooled tank to achieve extremely rapid oxidation treatment, thereby forming a dense and wear-resistant oxide layer.
Through this method, the wear resistance of the high-entropy alloy is significantly improved, the peeling or debris of the oxide layer is avoided, the service life of the implant is extended, and the excellent room temperature plasticity of the alloy is maintained.
Smart Images

Figure CN118703914B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy surface modification, and in particular to a method for improving the wear resistance of a high-plasticity refractory high-entropy alloy, a high-entropy alloy and applications. Background Art
[0002] For biomedical implant applications such as orthopedics and dentistry, alloys are required to have high strength plasticity and low elastic modulus to reduce stress shielding problems caused by alloy implants. CoCrMo alloy has excellent wear resistance and is used to manufacture artificial joints, but its biocompatibility is poorer than that of titanium alloys. The development of titanium alloys, especially metastable β titanium alloys in recent years, has achieved excellent biocompatibility and low modulus matching, but its wear resistance is poor, and it is easy to produce fine particles such as wear debris during long-term service in the body, causing inflammation.
[0003] High entropy alloys composed of refractory metal elements such as Ti, Zr, Hf, Nb and Ta with excellent biocompatibility have received widespread attention in recent years. Single-phase high entropy alloys such as TiZrNb, TiZrHfNb, TiZrHfNbTa have excellent strong plasticity, corrosion resistance, and lower elastic modulus than widely used dual-phase titanium alloys such as Ti-6Al-4V. However, its wear resistance is not much improved compared with conventional β-titanium alloys, and the low wear resistance limits the biological application of this type of alloy. Generally, surface modification processes such as spraying, laser cladding, and thermal oxidation can be used to improve the wear resistance of titanium alloy surfaces. In comparison, the cost of spraying and laser cladding processes is high and it is difficult to achieve parts with complex three-dimensional shapes. Compared with conventional medical alloys such as 316 stainless steel, CoCrMo and Ti-6Al-4V, the alloying of a large amount of active elements such as Zr, Hf and Ta makes this type of refractory high entropy alloy not resistant to high-temperature oxidation. During the conventional thermal oxidation process, on the one hand, rapid oxidation occurs, and a variety of oxides that are easy to fall off are generated on the alloy surface; on the other hand, the rapid diffusion of interstitial oxygen elements into the alloy block causes the overall embrittlement of the alloy, resulting in catastrophic oxidation damage.
[0004] After searching, the Chinese invention patent with application publication number CN113718190A discloses a method for improving the corrosion resistance and wear resistance of zirconium alloys with boiling nitric acid. By heating and keeping the zirconium alloy in a mixed gas and rapidly cooling it, an in-situ self-generated oxide film is formed on the surface of the zirconium alloy, and a dense and corrosion-resistant and wear-resistant protective layer is formed. This patent produces an in-situ self-generated oxide film on the surface of the zirconium alloy through a high-temperature heating, insulation and rapid cooling process. In the specific heat treatment process, the time control of heating and insulation is often subject to the size of the sample. The larger the sample, the longer the time it takes to heat and keep it to the preset temperature. This patent requires that the high-temperature oxidation treatment time of the sample cannot be too short, and its process is time-consuming. Summary of the invention
[0005] In view of the defects in the prior art, the purpose of the present invention is to provide a method for improving the wear resistance of a high-plasticity refractory high-entropy alloy, a high-entropy alloy and its application.
[0006] According to a first aspect of the present invention, there is provided a method for improving the wear resistance of a high-plasticity refractory high-entropy alloy, the method comprising:
[0007] Under the protection of inert gas, the heat treatment furnace is heated to a preset temperature and maintained at a constant temperature;
[0008] Placing the refractory high entropy alloy sample to be treated in the heating zone of the heat treatment furnace and keeping it warm for a preset time;
[0009] The refractory high entropy alloy sample is taken out and quickly placed in a water cooling tank to improve the wear resistance of the refractory high entropy alloy sample.
[0010] Optionally, the heat treatment furnace is heated to a preset temperature under the protection of an inert gas, wherein the inert gas is argon.
[0011] Optionally, the heat treatment furnace is heated to a preset temperature under the protection of an inert gas, wherein the heat treatment furnace is a tubular heat treatment furnace or a box-type heat treatment furnace.
[0012] Optionally, the heat treatment furnace is heated to a preset temperature under the protection of an inert gas and maintained at a constant temperature, wherein: the temperature range is 1000 to 1400° C., and the holding time is 10 to 20 minutes.
[0013] Optionally, the chemical formula of the refractory high entropy alloy sample is Ti a Zr b Hf c Nb d Ta e , wherein: a, b, c, d, e are atomic percentages, 20≤a≤40, 10≤b≤30, 0≤c≤30, 10≤d≤30, 0≤e≤40, and a+b+c+d+e=100.
[0014] Optionally, placing the refractory high entropy alloy sample to be treated in the heating zone of the heat treatment furnace includes: opening a plug at the gas outlet end of the heat treatment furnace before placing the refractory high entropy alloy sample, and quickly installing the plug after placing the refractory high entropy alloy sample.
[0015] Optionally, the insulation has a preset time length, wherein the insulation time is 5 minutes to 5 hours.
[0016] Optionally, the refractory high entropy alloy sample is taken out and quickly placed in a water cooling tank, wherein the temperature of the water cooling tank is room temperature.
[0017] According to a second aspect of the present invention, a high-plasticity refractory high-entropy alloy is provided, and the alloy is prepared by using the above-mentioned method for improving the wear resistance of the high-plasticity refractory high-entropy alloy.
[0018] According to the third aspect of the present invention, there is provided a high-plasticity refractory high-entropy alloy prepared by the method for improving the wear resistance of a high-plasticity refractory high-entropy alloy according to the first aspect, or the application of the high-plasticity refractory high-entropy alloy according to the second aspect in a biomedical implant material.
[0019] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0020] The present invention utilizes the extremely poor high-temperature oxidation resistance of refractory high-entropy alloys, and forms a dense wear-resistant oxide layer on the surface of the refractory high-entropy alloy through extremely rapid oxidation treatment. The wear-resistant oxide layer is tightly combined with the matrix alloy, which can avoid the peeling or generation of debris of the wear-resistant layer on the surface of the biomedical implant, thereby extending the service life of the refractory high-entropy alloy implant. In addition, compared with the traditional thermal oxidation surface treatment technology, the heat treatment technology of rapid surface oxidation of the present invention avoids the embrittlement tendency of the refractory high-entropy alloy matrix, and can ensure the excellent strength-plasticity matching of the entire implant while greatly improving the wear resistance of the refractory high-entropy alloy. The present invention helps to promote the application of refractory high-entropy alloys in the field of biomedical implants. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0022] Figure 1 A schematic diagram of a method for improving the wear resistance of a high-plasticity refractory high-entropy alloy in one embodiment of the present invention;
[0023] In the figure: 1 is a mechanical pump, 2 is a gas cylinder, 3 is a first stop valve, 4 is a second stop valve, 5 is a third stop valve, 6 is a vacuum gauge, 7 is a furnace body, 8 is a corundum tube, 9 is a plug, 10 is a fourth stop valve, and 11 is a water cooling tank;
[0024] Figure 2 In one embodiment of the present invention, Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 Comparison of the appearance of the alloy before and after rapid oxidation treatment;
[0025] Figure 3 In one embodiment of the present invention, Ti 20 Zr 20 Hf 20 Nb 20 Ta 20Scanning electron microscope microscopic morphology of the sample surface after rapid oxidation treatment of the alloy;
[0026] Figure 4 In one embodiment of the present invention, Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 Scanning electron microscope microscopic morphology of the cross section of the sample after rapid oxidation treatment of the alloy;
[0027] Figure 5 In one embodiment of the present invention, Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 Room temperature tensile property curve of the base alloy near the oxide layer of the sample after rapid oxidation treatment of the alloy;
[0028] Figure 6 In one embodiment of the present invention, Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 Grazing incidence X-ray diffraction patterns of the sample surface before and after rapid oxidation treatment of the alloy;
[0029] Figure 7 In one embodiment of the present invention, Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 Comparison of wear properties of alloy before and after rapid oxidation treatment. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0031] The embodiment of the present invention provides a method for improving the wear resistance of a high-plasticity refractory high-entropy alloy, the method comprising the following steps:
[0032] S1. Raise the temperature of the heat treatment furnace to a preset temperature under the protection of inert gas and maintain a constant temperature;
[0033] S2, placing the refractory high entropy alloy sample to be treated in the heating zone of the heat treatment furnace and keeping it warm for a preset time;
[0034] S3. Take out the refractory high entropy alloy sample and quickly place it in a water cooling tank to improve the wear resistance of the refractory high entropy alloy sample.
[0035] In the embodiment of the present invention, since an inert protective gas is introduced before the sample is placed in the heat treatment furnace, the refractory high entropy alloy sample can be prevented from being oxidized for a long time at high temperature during the heating and heat preservation process. By utilizing the extremely poor high-temperature oxidation resistance of the refractory high entropy alloy, the instantaneous surface rapid oxidation process of the sample from sampling to placing in the water cooling tank after high-temperature heat preservation is used to form a surface dense and wear-resistant oxide layer on the surface of the refractory high entropy alloy, thereby avoiding a large amount of oxygen elements at high temperature through the oxide layer to the matrix alloy. Diffusion, ensure the excellent room temperature plasticity of the matrix alloy, therefore, while greatly improving the wear resistance of the refractory high entropy alloy, the overall room temperature plasticity of the refractory high entropy alloy is not sacrificed, thereby preparing a refractory high entropy alloy with overall high plasticity and surface wear resistance in a relatively short time.
[0036] The heat treatment furnace in the embodiment of the present invention can be implemented by using existing technology. For example, refer to Figure 1 The heat treatment furnace includes a furnace body 7, a mechanical pump 1, a corundum tube 8, a gas cylinder 2, a vacuum gauge 6, a plug 9, a stop valve, etc. The corundum tube 8 is located in the furnace body 7 and is used to place the alloy sample to be treated; the mechanical pump 1 is used to extract the air in the corundum tube 8 to form a vacuum environment; the gas cylinder 2 is connected to the corundum tube 8 and is used to fill the corundum tube 8 with inert gas; the vacuum gauge 6 is used to obtain the pressure inside the furnace body 7; a first stop valve 3 is provided on the connecting pipeline between the mechanical pump 1 and the furnace body 7, a second stop valve 4 is provided on the connecting pipeline between the gas cylinder 2 and the furnace body 7, one end of the third stop valve 5 is respectively connected to the first stop valve 3 and the second stop valve 4, and the other end is connected to the vacuum gauge 6; a fourth stop valve 10 is provided at the outlet end of the furnace body 7; the plug 9 is provided at the gas outlet end of the corundum tube 8, and the plug 9 seals the corundum tube 8; in order to achieve extremely fast oxidation treatment of the alloy sample, a water cooling tank 11 is provided near the heat treatment furnace.
[0037] In some embodiments, the heat treatment furnace is heated to a preset temperature under the protection of an inert gas to prevent the sample from being oxidized during the high temperature insulation period. Preferably, the inert gas is argon, which has a low cost and good protective effect. The heat treatment furnace is a tubular heat treatment furnace or a box heat treatment furnace to form a high temperature closed environment and facilitate the introduction of inert gas.
[0038] In some embodiments, the heat treatment furnace is heated to a preset temperature under the protection of an inert gas and maintained at a constant temperature, wherein the preset temperature is determined according to the melting point of the refractory high entropy alloy, and the higher the melting point of the alloy, the higher the furnace temperature setting needs to be. Preferably, the temperature range is 1000-1400°C.
[0039] For example, for an equiatomic TiZrHfNbTa alloy, when the contents of refractory elements Ta and Nb in the alloy are moderate (20% each), depending on the size of the sample, the larger the sample, the longer the insulation time required. The heat treatment furnace with circulating inert gas protection conditions is heated to 1000°C to 1400°C. After the temperature rises to the preset temperature, it is kept warm for 10 to 20 minutes so that the entire sample obtains a uniform temperature.
[0040] In some embodiments, in order to achieve rapid oxidation treatment of the complex outer surface of the sample and improve the wear resistance, the refractory high entropy alloy sample is in the form of a block, and its chemical formula is Ti a Zr b Hf c Nb d Ta e , where: a, b, c, d, e are atomic percentages, 20≤a≤40, 10≤b≤30, 0≤c≤30, 10≤d≤30, 0≤e≤40, and a+b+c+d+e=100. The matrix alloys with this chemical formula have excellent biocompatibility while maintaining excellent mechanical properties, but these matrix alloys have poor wear resistance; in addition, the alloys corresponding to this chemical formula have poor oxidation resistance, and the oxidation process at high temperature progresses rapidly. The embodiments of the present invention utilize the above characteristics of the alloy matrix to prepare a wear-resistant oxide layer through extremely rapid oxidation treatment.
[0041] In some embodiments, the refractory high entropy alloy sample to be treated is placed in the heating zone of a heat treatment furnace, including: opening the plug at the gas outlet of the heat treatment furnace before placing the refractory high entropy alloy sample, and quickly installing the plug after placing the refractory high entropy alloy sample to form a sealed environment.
[0042] In some embodiments, in step S2, the holding time is 5 minutes to 5 hours according to the alloy composition, and the holding time can also play a role in element homogenization. Prolonging the holding time in this step is beneficial to improving the effect of element homogenization. If the content of high melting point elements such as Ta and Nb is high, the heating and holding time needs to be appropriately extended. The longer the time, the better the element homogenization effect.
[0043] Specifically, open the plug at the gas outlet of the heat treatment furnace, place the bulk refractory high entropy alloy sample that has been ultrasonically cleaned with anhydrous ethanol or acetone stably in the heating zone of the high-temperature heat treatment furnace, reinstall the plug of the heat treatment furnace, and keep it warm for 5 minutes to 5 hours.
[0044] In some embodiments, a refractory high entropy alloy sample is taken out and quickly placed in a water cooling tank, wherein the temperature of the water cooling tank is room temperature, generally around 25°C, and rapid cooling of the high-temperature bulk sample can be achieved through a simple process.
[0045] Specifically, the plug at the outlet end of the heat treatment furnace is removed again, the refractory high entropy alloy sample is taken out and quickly placed in a water cooling tank. During the process of sampling and placing it in the water cooling tank, the sample is exposed to the air for about 1 to 2 seconds. During this extremely short period of time, a dense and wear-resistant oxide scale is formed on the surface of the bulk alloy sample.
[0046] For the refractory high entropy alloy in the embodiment of the present invention, since its high temperature oxidation activity is much higher than that of zirconium alloy, if the treatment method of the prior art (such as CN113718190A) is adopted, uncontrollable oxidation will occur, causing the oxide layer to thicken and peel off rapidly, and also causing a large amount of oxygen elements to diffuse into the high entropy alloy matrix, resulting in embrittlement of the matrix alloy. The embodiment of the present invention places the heating and heat preservation links under the protection of inert gas, avoiding the above negative effects caused by long-term oxidation, thereby ensuring the excellent room temperature plasticity of the alloy matrix.
[0047] Compared to existing surface modification process technologies such as thermal spraying and laser cladding, the embodiments of the present invention utilize the extremely poor high-temperature oxidation resistance of refractory high-entropy alloys, and form a dense wear-resistant oxide layer on the surface of the refractory high-entropy alloy through extremely rapid oxidation treatment. The wear-resistant oxide layer is tightly combined with the matrix alloy, which can avoid the peeling or generation of debris of the wear-resistant layer on the surface of the biomedical implant, thereby extending the service life of the refractory high-entropy alloy implant. In addition, compared with traditional thermal oxidation surface treatment technology, the heat treatment technology of rapid surface oxidation in the embodiments of the present invention avoids the embrittlement tendency of the refractory high-entropy alloy matrix, and can ensure the excellent strength-plasticity matching of the entire implant while greatly improving the wear resistance of the refractory high-entropy alloy. The embodiments of the present invention are helpful to promote the application of refractory high-entropy alloys in the field of biomedical implants.
[0048] Another embodiment of the present invention provides a high-plasticity refractory high-entropy alloy, which is prepared by the above method. The alloy combines the excellent room temperature plasticity and high wear resistance of the refractory high-entropy alloy.
[0049] Another embodiment of the present invention also provides an application of the above-mentioned high-plasticity refractory high-entropy alloy in biomedical implant materials. Specifically, it can be applied to biomedical implant materials such as orthopedics and dentistry. Due to its high wear resistance, it can serve in the body for a long time.
[0050] The scheme of the present application will be explained below in conjunction with specific embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the documents in this area or the product specifications are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained through commercial channels.
[0051] Continue to refer to Figure 1In a specific embodiment, the method for improving the wear resistance of a high-plasticity refractory high-entropy alloy comprises the following steps:
[0052] 1) Turn on the power of the heat treatment furnace, raise the temperature of the heat treatment furnace to 1300℃, and keep it warm for 20 minutes.
[0053] 2) Close the second stop valve 4 and the fourth stop valve 10, open the first stop valve 3 and the third stop valve 5, and use the mechanical pump 1 to extract the air in the corundum tube 8 for 10 minutes, so that the reading of the vacuum gauge 6 drops to the minimum negative pressure. Close the first stop valve 3, open the second stop valve 4 to backfill the corundum tube 8 with argon gas to a positive pressure, and then quickly open the fourth stop valve 10 to maintain a slight positive pressure (0.02MPa) in the entire corundum tube 8 for 5 minutes.
[0054] 3) Remove the plug 9 at the right end of the corundum tube 8 and ultrasonically clean the Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 The alloy sample is placed in the heating zone in the middle of the corundum tube 8; then the plug 9 is reinstalled, and the positive pressure argon atmosphere is maintained, and the temperature is kept for 30 minutes.
[0055] 4) Remove the plug 9 on the right end of the heat treatment furnace again, take out the sample and quickly place it in a water-cooling tank 11 filled with water on the ground. During the process of the refractory high entropy alloy sample being transferred from the high-temperature circulating atmosphere furnace to the water-cooling tank 11, the sample is exposed to air for about 1 to 2 seconds. In this extremely short period of time, a dense and wear-resistant oxide layer can be formed on the surface of the alloy.
[0056] In order to verify that the method of the embodiment of the present invention forms a dense wear-resistant oxide layer on the alloy surface, the alloy samples were tested before and after rapid oxidation treatment, and the results are as follows.
[0057] Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 Comparison of the appearance of the alloy before and after rapid oxidation treatment Figure 2 As shown. The left side is the original flaky alloy sample with a diameter of 25mm and a thickness of 4mm. The original alloy sample was cut from the alloy ingot using wire cutting and polished with 120#, 400#, 800#, and 1200# sandpaper respectively. The right side shows the appearance of the flaky alloy sample after rapid oxidation heat treatment. The alloy is surrounded by a dense oxide layer. The slight difference in the thickness of the oxide layer leads to the difference in color in different areas.
[0058] Ti 20 Zr 20 Hf 20Nb 20 Ta 20 The scanning electron microscope microstructure of the sample surface after rapid oxidation treatment of the alloy is as follows: Figure 3 As shown. The sample after rapid oxidation was directly placed under a scanning electron microscope for observation. The left picture shows the morphology of the oxide layer at 5000X magnification. The oxide in the high-temperature rapid oxidation process grows in a typical step-like manner. The right picture shows the morphology of the oxide layer at 30000X magnification, which shows that the oxide layer has a phenomenon of selective oxidation at the nanoscale.
[0059] Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 The scanning electron microscope microstructure of the cross section of the alloy after rapid oxidation treatment is as follows: Figure 4 As shown in the figure, the sheet sample after rapid oxidation was wire cut, hot mounted, and then sanded with 120#, 400#, 800#, 1200#, and 2000# sandpaper and mechanically polished. It can be seen that the thickness of the oxide layer is 3 to 5 μm.
[0060] Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 The room temperature tensile mechanical properties curve of the base alloy near the oxide layer after rapid oxidation treatment is as follows: Figure 5 As shown, after wire cutting, grinding off the oxide layer on the surface, and polishing with 120#, 400#, and 800# sandpaper in sequence and stretching at room temperature, it can be seen that the matrix alloy near the oxide layer still maintains an elongation of more than 15%, reflecting the excellent room temperature plasticity of the matrix alloy after oxidation.
[0061] Ti 20 Zr 20 Hf 20 Nb 20 Ta 20 The grazing incidence X-ray diffraction patterns of the sample surface before and after rapid oxidation treatment of the alloy are as follows: Figure 6 As shown in the figure, before the rapid oxidation treatment, the grazing incidence X-ray spectrum of the sample surface shows that the initial alloy is a single-phase body-centered cubic structure (BCC). After the surface thermal oxidation, it can be observed that the surface layer of the alloy surface after rapid oxidation is composed of HfO2, ZrO2, Nb2O5 and Nb2Zr6O 17 Composed of four types of oxides.
[0062] Ti 20 Zr 20 Hf 20 Nb 20 Ta 20Comparison of wear properties of alloys before and after rapid oxidation treatment Figure 7 As shown in the figure, it can be seen that the wear scar depth decreases significantly after rapid oxidation treatment. 20 Zr 20 Hf 20 Nb 20 Ta 20 The wear volume of the alloy (68.7×10 -5 mm -3 N -1 m -1 ), the wear loss of the alloy after rapid oxidation decreased to 3.2×10 -5 mm -3 N -1 m -1 .
[0063] In the above embodiment of the present invention, the refractory high entropy alloy is placed in a high-temperature heat treatment furnace protected by a circulating inert gas, and then the high-temperature sample is taken out and quickly water-cooled. In the extremely fast process of high-temperature sampling-water cooling, a dense and wear-resistant surface oxide layer can be formed on the surface of the alloy. The embodiment of the present invention can greatly improve the wear resistance of the alloy while ensuring the excellent room temperature plasticity of the refractory high entropy alloy. The method in the embodiment of the present invention is widely applicable to various types of high-plasticity refractory high entropy alloys, has low cost and simple process flow, is suitable for improving the surface wear resistance of parts with complex surface shapes, and has broad application prospects in the fields of biomedical implants, harsh friction and wear, etc.
[0064] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essence of the present invention. The above preferred features can be used in any combination without conflicting with each other.
Claims
1. A method for improving the wear resistance of a high-plasticity refractory high-entropy alloy, characterized in that: include: Under the protection of inert gas, the heat treatment furnace is heated to a preset temperature and maintained at a constant temperature; the inert gas is argon, the temperature range is 1000-1400°C, and the holding time is 10-20 minutes; The refractory high entropy alloy sample to be treated is placed in the heating zone of the heat treatment furnace and kept warm for a preset time; the chemical formula of the refractory high entropy alloy sample is Ti a Zr b Hf c Nb d Ta e , where: a, b, c, d, e are atomic percentages, a, b, c, d, e are all 20; the insulation time is 5 minutes to 5 hours; The refractory high entropy alloy sample is taken out and quickly placed in a water cooling tank, the temperature of the water cooling tank is room temperature, and the sample is in contact with air for 1 to 2 seconds during the process of sampling and placing in the water cooling tank, so as to improve the wear resistance of the refractory high entropy alloy sample.
2. The method for improving the wear resistance of a high-plasticity refractory high-entropy alloy according to claim 1, characterized in that: The heat treatment furnace is heated to a preset temperature under the protection of an inert gas, wherein the heat treatment furnace is a tubular heat treatment furnace or a box-type heat treatment furnace.
3. The method for improving the wear resistance of high-plasticity refractory high-entropy alloy according to claim 1, characterized in that: Placing the refractory high entropy alloy sample to be treated in the heating zone of the heat treatment furnace comprises: opening a plug at the gas outlet end of the heat treatment furnace before placing the refractory high entropy alloy sample, and quickly installing the plug after placing the refractory high entropy alloy sample.
4. A high plasticity refractory high entropy alloy, characterized in that: The alloy is prepared by the method for improving the wear resistance of a high-plasticity refractory high-entropy alloy as described in any one of claims 1 to 3.
5. A method for improving the wear resistance of a high-plasticity refractory high-entropy alloy prepared by the method for improving the wear resistance of a high-plasticity refractory high-entropy alloy as described in any one of claims 1 to 3, or an application of the high-plasticity refractory high-entropy alloy as described in claim 4 in biomedical implant materials.
Citation Information
Patent Citations
Method for improving boiling nitric acid corrosion resistance and wear resistance of zirconium alloy
CN113718190A